Трудове право та кадрове адміністрування в системі управління HR - Тур, Олеся Василівна; Тюха, Ірина Володимирівна; Шереметинська (Горобець), Оксана Валеріївна (My University, 2022)
У даній статті представлено правові аспекти регулювання трудових відносини, а також інших видів відносин пов’язаних з ними і обумовлених їх існуванням. Виявлено, що правове регулювання роботи з людськими ресурсами здійснюється на основі державного, адміністративного і трудового права. Значну увагу приділено трудовому праву та кадровому адмініструванню в системі управління HR. Розглянуто основні методи планування і прогнозування, які використовуються в кадровому адмініструванні. Визначено, що в кадровому адмініструванні об’єктом є персонал, а суб’єктом - працівники. Розглянуто основні характеристики кадрового адміністрування та аспекти управління персоналом до яких належать: техніко-технологічний; організаційно-економічний; правовий; соціально-психологічний; педагогічний. Приділено значну увагу правовому аспекту управління персоналу на основі міжнародного законодавства та трудового права України. Виявлено, що регулювання трудових відносин як працівників, так і роботодавців, здійснюється трудовим договором. Також розглянуто сутність трудового договору та його терміни. This article presents the legal aspects of regulating labor relations, as well as other types of relations related to them and conditioned by their existence. It was found that the legal regulation of work with human resources is carried out on the basis of state, administrative and labor law. Considerable attention is paid to labor law and personnel administration in the HR management system, since labor law regulates employee-employer relations, and personnel administration is aimed at organizational and legal support of personnel management processes, which allows to increase labor productivity and the quality of its work, which affects the general economic enterprise efficiency. The main planning and forecasting methods used in personnel administration are considered. It was determined that in personnel administration, the object is personnel, and the subject is employees. The main characteristics of personnel administration are considered, namely: analysis of the need for personnel; determination of personnel requirements; determination of the main sources of income of candidates; development and selection of recruitment methods; and aspects of personnel management, which include: technical and technological; organizational and economic; legal; socio-psychological; pedagogical. Considerable attention is paid to the legal aspect of personnel management based on the analysis of international legislation, namely: the Universal Declaration of Human Rights, adopted by the UN General Assembly on December 10, 1948; International Covenant on Economic, Social and Cultural Rights, adopted by the UN General Assembly on December 16, 1966; of the European Social Charter of May 3, 1996; and labor law of Ukraine. It was determined that not only labor relations are the scope of application of labor law, but also all other types of relations are related to them and conditioned by their existence, and their termination leads to the termination of other relations related to them. It was found that the regulation of labor relations of both employees and employers is carried out by an employment contract, which is concluded in personnel services by employees of the enterprise. The essence of the employment contract, its terms and forms of conclusion are also considered.
Keywords: трудові відносини; управління трудовими ресурсами; трудове право; кадрове адміністрування; діловодство; трудовий договір; labor resources management; labor contract; labor relations; labor law; personnel administration; кафедра економіки праці та менеджменту